An analysis of the current perspective and review regarding bone metastasis in colorectal adenocarcinoma - Bagus, Budhi Ida; Setyono, Hanis; Suwardi; Wibisono (International Surgery Journal, 2025)
In developed regions, colorectal cancer (CRC) is the third most common cause of cancer-related death, with 1.2 million new cases diagnosed annually worldwide. Six percent of all CRC metastases are bone metastases. Remarkably, 70% of patients develop distant metastases during follow-up, and 22% of patients show them at diagnosis. Bone metastases indicate a worsened oncological prognosis, even though they are rare. Six percent of all CRC metastases are bone metastases. Treating CRC that has spread to the bones can be difficult and frequently signals an advanced stage of the disease. Since the bone is frequently the site of metastasis for a variety of primary tumours, including breast, prostate, lung, thyroid, and kidney cancer, managing bone metastases is a crucial component of cancer care. In addition to reducing pain and complications, effective treatment of bone metastases can enhance patients’ quality of life.